A new cytochalasin derivative from the mangrove-derived endophytic fungus Xylaria sp. HNWSW-2. Issue 10 (3rd October 2018) - Wang, Pei; Cui, Yan; Cai, Cai-Hong; Kong, Fang-Dong; Chen, Hui-Qin; Zhou, Li-Man; Song, Xin-Ming; Mei, Wen-Li; Dai, Hao-Fu
Abstract: A new cytochalasin derivative xylarisin B (1 ), together with four known compounds astropyrone (2 ), guaidiol (3 ), xylaropyrone B (4 ), and xylaropyrone C (5 ), were isolated from the fermentation broth of Xylaria sp. HNWSW-2. Their structures were elucidated by spectroscopic data. Among them, compounds2 and3 at a concentration of 50 μg/ml showed weak inhibitory activity against AChE with inhibition rates of 10.4 and 12.9%, respectively. In addition, compound2 also exhibited inhibitory activity against α-glycosidase with inhibition rate of 77.0% at a concentration of 0.25 mg/ml.